Flexible Baseband-Unit Aggregation Enabled by Reconfigurable Multi-IF Over WDM Fronthaul - Haiyun Xin; Hao He; Kuo Zhang; Syed Baqar Hussain; Weisheng Hu (IEEE Photonics Journal)
In cloud-radio access network, baseband-unit (BBU) aggregation schemes have been intensively discussed to improve the efficiency of resources in light traffic times. Also, driven by the emerging optical fronthaul, traffic migration is introduced in optical fronthaul to help realize BBU aggregation, based on which traffic exchange within BBU pool can be reduced, thus decreasing corresponding processing latency and energy consumption. However, these traffic migration schemes are operated in a time-division multiplexing way and are not suitable for multi-IF over wavelength-division multiplexing (WDM) fronthaul. In this paper, we propose a reconfigurable multi-IF over WDM fronthaul to support BBU aggregation. Based on IF traffic migration and optical path reconfiguration, traffic of multiple cell sites can be routed to one BBU to achieve BBU aggregation. Proof-of-concept experiments are demonstrated to verify the feasibility of the proposed architecture. For 4G+ deployment as specified in 3GPP protocol, 100-MHz orthogonal frequency-division multiplexing signal with 64 quadratic-amplitude modulation format after transmission shows that 3.5% error vector magnitude can be achieved.